Effects of family and neighborhood risks on glycemic control among young black adolescents with type 1 diabetes: Findings from a multi‐center study. Issue 3 (16th January 2021) - Ellis, Deborah A; Cutchin, Malcolm P; Templin, Thomas; Carcone, April Idalski; Evans, Meredyth; Weissberg‐Benchell, Jill; Buggs‐Saxton, Colleen; Boucher‐Berry, Claudia; Miller, Jennifer L; Al Wazeer, Mouhammad; Gharib, Jamil; Mehmood, Yasir; et al.
Abstract: While individual and family risk factors that contribute to health disparities in children with type 1 diabetes have been identified, studies on the effects of neighborhood risk factors on glycemic control are limited, particularly in minority samples. This cross‐sectional study tested associations between family conflict, neighborhood adversity and glycemic outcomes (HbA1c) in a sample of urban, young Black adolescents with type 1 diabetes(mean age = 13.4 ± 1.7), as well as whether neighborhood adversity moderated the relationship between family conflict and HbA1c. Participants ( N = 128) were recruited from five pediatric diabetes clinics in two major metropolitan US cities. Diabetes‐related family conflict was measured via self‐report questionnaire (Diabetes Family Conflict Scale; DFCS). Neighborhood adversity was calculated at the census block group level based on US census data. Indictors of adversity were used to calculate a neighborhood adversity index (NAI) for each participant. Median family income was 25, 000, suggesting a low SES sample. In multiple regression analyses, DFCS and NAI both had significant, independent effects on glycemic control ( β = 0.174, P = 0.034 and β = 0.226 P = 0.013, respectively) after controlling for child age, family socioeconomic status and insulin management regimen. Tests of effects of the NAI and DFCS interaction on HbA1c found no significant moderating effects of neighborhood adversity. Even within contexts of significant socioeconomic disadvantage, variability in degree of neighborhood adversity predicts diabetes‐related health outcomes in young Black adolescents with type 1 diabetes. Providers should assess social determinants of health such as neighborhood resources that may impact adolescents' ability to maintain optimal glycemic control.